IMPLEMENTASI METODE GRAMATIKA TARJAMAH DALAM PEMBELAJARAN QIRA’AH DAN KITABAH - Zaenudin, Udin (Program Studi Pendidikan Agama Islam, 2025)
This research explains how the translated grammatical method applies to Arabic language learning at the Tasikmalaya Islamic Institute PAI Study Program with a problem focus: How the translated grammatical method is implemented in Maharat Qira'ah and Kitabah learning carried out by Arabic language teaching lecturers, and the factors that influence it. . The subject of this research is a lecturer who teaches Arabic, while the object of this research is the implementation of the Translated Grammatical Method in teaching Maharat Qira'ah and Kitabah in Arabic Language Learning as well as supporting and inhibiting factors in its implementation. The data collection techniques used in this research are observation, interview and documentation techniques. Data processing is achieved through collection, editing, classification and interpretation. Data analysis uses qualitative data by describing actual events in the form of sentence descriptions, and in drawing conclusions the author uses an inductive method, namely drawing conclusions from specific to general things. The results of this research indicate that the Translated Grammatical Method in delivering Arabic language material is fully in accordance with the steps of the Translated Grammatical Method. This can be seen from the planning stage which includes: creating a Semester Learning Plan, annual program, universal program and syllabus, as well as providing adequate learning facilities. Next, the implementation stage carried out by the Arabic Language Lecturer is in accordance with the principles of implementing the Translated Grammar Method with an appropriate semester learning plan. The supporting and inhibiting factors for the Translated Grammar Method in Arabic Language Learning at the Tasikmalaya Islamic Institute PAI Study Program are the lecturers' educational background, the lecturers' teaching experience following training, the lecturers' knowledge of learning strategies, intelligence and students' interest in learning